A highly sensitive and multi-responsive Tb-MOF fluorescent sensor for the detection of Pb2+, Cr2O72−, B4O72−, aniline, nitrobenzene and cefixime. (December 2021) - Chen, Xiao-Li; Shang, Lu; Liu, Lu; Yang, Hua; Cui, Hua-Li; Wang, Ji-Jiang
Abstract: A terbium metal organic framework (Tb-MOF), namely {[Tb(dppa)(H2 O)2 ]·dima·H2 O·0.5O}n (1 ), (H4 dppa = 5-(3′4′-dicarboxylphenoxy)isophthalic acid, dima = dimethylamine, which is formed by the decomposition of DMF in aqueous solution at high temperature.) was prepared and characterized. Tb-MOF is connected by (dppa) 4- ligands via μ4 :η 1, η 2, η 2, η 2 coordination mode to form a two-dimensional wavy network, which is extended to three-dimensional supramolecular structures based on hydrogen bonding. Tb-MOF has excellent fluorescence properties, which can be used for fluorescence recognition and quantitative determination of cation and anion, antibiotics and small organic molecules in aqueous solution with high sensitivity and good selectivity. Tb-MOF showed enhanced fluorescene for Pb 2+ and B4 O7 2− ions, while quenching fluorescence for Cr2 O7 2− ion. Noticeably, this is the first time that Pb 2+ and B4 O7 2− ions have been detected by a MOF-based fluorescence sensor using a fluorescence enhancement mechanism. More interestingly, Tb-MOF can quantitatively detect aniline (ANI) in aqueous solution by ratiometric fluorescence sensing. In addition, Tb-MOF has great selectivity and sensitivity for detecting of nitrobenzene (NB) and cefixime (CEF). In particular, when NB concentration is 50 μM, the fluorescence quenching rate of Tb-MOF reaches 99.6%. Therefore, this paper introduces a highly sensitive and multi-responsive Tb-MOF sensor, which can be used to detect Pb 2+, B4 O7 2−, Cr2 O7 2−, ANI, NB and CEF with fast response speed and good selectivity. Highlights: A Tb-MOF based on H4 dppa and dima ligands was obtained and characterized. Tb-MOF shows a 2D wavy network structure. Tb-MOF has excellent fluorescence properties. Tb-MOF sensor can be used to detect Pb 2+, Cr2 O7 2−, B4 O7 2−, aniline, nitrobenzene and cefixime with fast response, high sensitivity and good selectivity. The possible fluorescence sensing mechanisms of analytes are discussed in detail.